The role of coagulation in the temperature-sensitive PVDF-g-PNIPAAm membrane properties. Issue 36 (1st August 2016) - Li, Zhan; Wang, Qian; Chen, Xi; Lai, Shuyi; Feng, Xia; Zhao, Yiping; Chen, Li
Abstract: An amphiphilic copolymer (PVDF-g-PNIPAAm) with poly (vinylidene fluoride) (PVDF) main chains and poly (N-isopropylacrylamide) (PNIPAAm) side chains was synthesized by free-radical polymerization, and flat sheet copolymer membranes were prepared via the phase inversion method with N, N-dimethylformamide (DMF) as the solvent and DMF/water as the coagulation bath. The influence of the coagulation bath composition on the structure and properties of PVDF-g-PNIPAAm membrane was studied. The structure and performance of membranes were characterized by X-ray photoelectron spectroscopy, scanning electron microscopy, contact angle test, and filtration experiment. The results showed that the coagulation bath composition could affect the resulting membrane properties including pore structure, hydrophilicity, permeability, and temperature sensitivity. The PVDF-g-PNIPAAm membrane prepared in 5 wt% DMF coagulation bath exhibited higher water flux and obvious temperature sensitivity.